Symbolic Chiasm in Arvo Pärt’s Passio (1982) - Vuorinen, Mark (Circuit, 2011)
Passio, is Arvo Pärt’s first large scale vocal-instrumental work in the tintinnabuli style and remains today one of his most significant compositions. In this setting of the Passion text according to St. John, Pärt codifies procedures of tintinnabuli that will remain his principle means of musical communication for years to come while implying a very important perspective of Johannine theology. His compositional design utilizes both small-scale and large-scale chiastic constructions and gives prominence to John’s observance in Chapter 18, verse 4, that Christ knows all that will occur in the events leading to his crucifixion. Seen in this light, the Passion narrative unfolds according to a pre-ordained plan; it is this subtle perspective of the Gospel that Arvo Pärt reveals musically in his Passio. This paper approaches a musical analysis of Passio in relation to John’s perspective that Christ knew all that was to follow. It illustrates that virtually every note is linked in some way to Pärt’s musical pilgrimage to the cross. With a microscopic lens, the analysis connects Pärt’s use of melody, texture, inversion and tintinnabuli to a poignant marriage of music and the biblical text. And on a macroscopic level, it is shown that musical events unfold over time to reveal the inevitability of the crucifixion. It is revealed that within the work’s tonal centres, large-scale textural procedures, pedal points and the music of the Exordium and Conclusio the path to the cross is present from beginning to end. In this way, the listener is taken through the narrative only to realize afterward that the Gospel’s outcome was present from beginning to end.